Bacteriological Analysis of Vegetables found in Kathmandu Valley (Tribhuvan University Journal of Microbiology, 2024)
Objectives: The study was conducted to determine the bacteriological analysis of vegetables by comparing the number of bacterial count between farm and market along with antibiotic susceptibility pattern of the isolates and evaluate the status of MDR and MRSA.Methods: The cross-sectional study was done from February to July of 2023. A total of 60 samples were gathered from three distinct districts: Kathmandu, Bhaktapur, and Lalitpur, consisting of 10 samples from each farm and market and the research was carried out at the Nepalese Farming Institute, Kathmandu. The bacterial count was compared and identified by standard microbiological approaches such as serial dilution, spread plate method, and other biochemical tests. The antimicrobial profile was carried out by the Kirby-Bauer disc diffusion method to analyze the status of MDR and MRSA.Results: From all 60 samples the highest total plate count and total coliform count (mean) was found in spinach (9.3×106) and cabbage (4.9×106) from market. A total of 35 bacteria were identified i.e. 16 (46%) from farms including E. coli, Klebsiella spp., Pseudomonas spp. and Staphylococcus aureus and 19(54%) from markets such as E. coli, Klebsiella spp., Pseudomonas spp., Serratia spp. and Staphylococcus aureus. Antibiotic susceptibility pattern shown that Tetracycline was the most effective antibiotic as 80% Enterobacteriaceace isolates were sensitive but contradicted to Serratia marcescens and S. aureus was 100% susceptible to Linezolid, Cotrimoxazole followed by Gentamicin and Tetracycline. Out of 35 isolates, 14 showed MDR Strains i.e., Enterobacteriaceace (n=7; 35%) and S. aureus (n=7; 46.67%) and 3 isolates were screened as suspected ESBL producers but none were confirmed. A total of 15 S. aureus were isolated; among which 12 exhibited methicillin resistance (MRSA).Conclusion: The present study shows that the vegetables from the studied area contain a wide variety of bacteria raising significant public health concerns. It highlights the need for improved protocols and practices throughout the entire process of vegetable production, distribution and consumption.